The Impact of Outsourcing on Airlines’ Performance: Empirical Evidence from Asia and Countries in the Pacific - Muhammad Asraf, Bin Abdullah; NurulHuda, Binti Mohd Satar (Emerald Publishing Limited, 2018)
This chapter examines the influence of outsourcing on airlines’ performance from countries of the Asia Pacific region. Performance in the context of this study is drawn from productivity growth and technical efficiency scores that are calculated using the standard data envelopment analysis (DEA) approach. We utilize data from airlines over the period 2003–2011 and estimate the impact of outsourcing on productivity and technical efficiency using generalized method of moments (GMM) estimators. The findings from DEA reveal an improvement in the technical efficiency score of airlines from Asia Pacific. Nonetheless, productivity estimates indicate fluctuations in the productivity growth trend of airlines, attributable to global economic recession in 2007/2008. GMM estimation results, however, suggest negative impacts of outsourcing on technical efficiency and productivity of the airlines from Asia Pacific countries. We offer several explanations for these outsourcing findings. Heavy outsourcing of airlines activities particularly maintenance of aircraft may negatively affect aircraft utilization and ultimately erode the service level of airlines. The erosion of the service level of airlines would affect the demand for air travel in a downward manner, thereby lowering the technical efficiency and productivity of airlines. Also, relatively low labor costs enjoyed by airlines in the Asia Pacific region would suggest that having many airline activities in-house would save operating expenses attributable to labor costs.